Social Media and Human Trafficking: Using Social Media in Education of Human Trafficking Case Study on Operation Underground Railroads (Ours) - Hadjira Sitti; Anggreyani Reysa; Halida Rahmi Tazkia; Nur Fitria Fadhila; Suranto; Jorgi Sutan Arissy (E3S Web of Conferences, 2023)
Social media is a powerful platform for disseminating information about human trafficking regardless of regional boundaries. So it is necessary to see the role of social media in increasing public knowledge through education provided by social media platforms, one of which is how social media OURrescue to eradicate acts of human trafficking. This research will aim to see how Twitter social media in Operation Underground Railroads (Ours) increases public knowledge about the issue of human trafficking by concentrating on three main issues: Social media content, OURrescue social media account activity, and The influence of narratives in providing education related to human trafficking to the public through social media. The qualitative method is the method taken in this study which uses a data analysis approach, namely Qualitative Data Analysis Software (Q-DAS), explicitly using the Nvivo 12Plus application through qualitative descriptive. The results of this study have three main points: First, in the content dichotomy, the @OURrescue account has participated in combating human trafficking. Second, the @OURrescue account in disseminating information and education to the public still needs to be more consistent than in 2016, which was very active in social media. Third, the @OURrescue account shows the dissemination of narratives related to the fight against human trafficking and plays a role in establishing relationships with actors who often raise issues of human trafficking. Focusing on research on human rights which is analysed through Twitter social media, shows a novelty from this research.